Estudo in vitro de potenciais biomarcadores de nefrotoxicidade por expressão gênica diferencial usando gentamicina - Sarah Cristina Teixeira Silva (2014)
Drug-induced nephrotoxicity is one of the most frequently observed effects in long-term pharmacotherapy and in the early preclinical phase of drug development. The development of more specific bioactive molecules for therapeutic use has been difficult due to the incidence of adverse reactions. The effects of nephrotoxicity are commonly discovered later due to lack of sensitivity of in vivo methods to evaluate this effect. Therefore, researchers have tried to develop in vitro alternative methods for early identification of toxicity. Identification of drug-induced gene changes is critical to provide insights into molecular mechanisms and to detecting renal damage. Gentamicin, for example, is a widely used aminoglycoside antibiotic that causes nephrotoxicity. In the present study, LLC-PK1 cells were exposed for 24 h to gentamicin concentrations of 4 (low), 8 (medium), and 12 (high) mM, according to MTT tests, to evaluate differential gene expression. A literature survey was conduced to identify genes associated with the development of nephrotoxicity. A panel of genes was selected based on genes expression changes in multiple published studies. Due to limited base of study for the cellular model in this work, the search for sequences of mRNAs encoding proteins that had been previously associated with kidney damage was researched in the databases of the National Center for Biotechnology Information - NCBI (USA). The primers were obtained using the Primer BLAST (NCBI) program, based on the sequences of selected transcripts. RNA was extracted from the cells, and RT-PCR was performed to evaluate expression profiles of the selected genes. Among the analyzed genes, four genes proved to be highly differential up-regulated in cells exposed to the nephrotoxin: HAVcr-1 (hepatitis A vírus cellular receptor 1), CASP3 (caspase1), ICAM-1 (intracellular adhesion molecule 1) and EXOC3 (exocyst complex component 3). According to the obtained results, it can be suggested that these genes can be used as early in vitro biomarkers for the identification of nephrotoxicity. The establishment of genomic markers is a promising tool for evaluating nephrotoxicity and will be useful in the development of safer drugs.